2013
DOI: 10.5936/csbj.201301010
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Methods for Omics and Knowledge of Crude Medicinal Plants Toward Big Data Biology

Abstract: Molecular biological data has rapidly increased with the recent progress of the Omics fields, e.g., genomics, transcriptomics, proteomics and metabolomics that necessitates the development of databases and methods for efficient storage, retrieval, integration and analysis of massive data. The present study reviews the usage of KNApSAcK Family DB in metabolomics and related area, discusses several statistical methods for handling multivariate data and shows their application on Indonesian blended herbal medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 131 publications
(119 reference statements)
0
28
0
1
Order By: Relevance
“…This situation is also a feature of the ethnomedicinal survey as the number of medicinal plants is estimated to be 40,000-70,000 around the world [121] and many countries utilize these plants as blended herbal medicines, e.g., China (traditional Chinese medicine), Japan (Kampo medicine), India (Ayurveda, Siddha and Unani) and Indonesia (Jamu). In [87], authors reviewed the usage of KNApSAcK Family DB in metabolomics and related area, discussed several statistical methods for handling multivariate data and showed their application on Indonesian blended herbal medicines (Jamu) as a case study. Exploration using Biplot (a multivariate exploration tool) revealed that many plants are rarely utilized while some plants are highly utilized toward specific efficacy.…”
Section: Biochemistry Genetics and Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is also a feature of the ethnomedicinal survey as the number of medicinal plants is estimated to be 40,000-70,000 around the world [121] and many countries utilize these plants as blended herbal medicines, e.g., China (traditional Chinese medicine), Japan (Kampo medicine), India (Ayurveda, Siddha and Unani) and Indonesia (Jamu). In [87], authors reviewed the usage of KNApSAcK Family DB in metabolomics and related area, discussed several statistical methods for handling multivariate data and showed their application on Indonesian blended herbal medicines (Jamu) as a case study. Exploration using Biplot (a multivariate exploration tool) revealed that many plants are rarely utilized while some plants are highly utilized toward specific efficacy.…”
Section: Biochemistry Genetics and Molecular Biologymentioning
confidence: 99%
“…Literature on Big Data had a growth of more than 150 % from 2012 to 2014. Research papers addressed the challenges of capturing [75], storing [76,77], searching [78], sharing [23], analyzing [9,79] and visualizing [80,81] Big Data sets in several fields such as Computer Science [82,83]; Mathematics [63]; Business, Management and Accounting [41]; Engineering [84]; Physics and Astronomy [85,86]; Biochemistry, Molecular Biology and Genetics [87]; Medicine [88]; Social Sciences [89,90]; Materials Science [24]; Decision Sciences [91], and Arts and Humanities [92]. It is important to consider the distribution of papers by publisher to determine the paper focus: the challenge addressed by the works and the domain considered.…”
Section: Classification Of Research Papersmentioning
confidence: 99%
“…Data mining is the process of sorting through large datasets to identify patterns and establish relationships to solve problems through data analysis by using machine-learning and statistical methods (Afendi et al, 2013;Yea et al, 2016). Data mining methods use various kinds of information obtained from sources such as bibliographic literature, experimental data, clinical data, and curated data.…”
Section: Role Of Data Mining In Medicinal Plant Selectionmentioning
confidence: 99%
“…Analisis terhadap basisdata mengenai jamu untuk mendapatkan korelasi antara tanaman, jamu, dan korelasi antara tanaman, jamu, dan khasiat tentang jamu dilakukan dengan menggunakan model statistik [13] [14]. Metode yang digunakan adalah Biplot, Partial Least Square (PLS) dan metode bootstrapping untuk membuat kesimpulan dan fokus pada prediksi untuk membuat formula jamu.…”
Section: ( )unclassified